A Mobile Based Technology to Improve Male Involvement in Antenatal Care. - Muhoza, B. Gloria; Ssemaluulu, Paul Mukasa; Mabirizi, Vicent (Kabale University, 2024)
The World Health Organization Technical Working Group on maternal health unit recommended a minimum level of care to be four visits throughout the pregnancy for pregnant mothers [1]. The first visit which is expected to screen and treat anaemia, and syphilis, screen for risk factors and medical conditions that can be best dealt with in early pregnancy and initiate prophylaxis if required (e.g., for anaemia and malaria) is recommended to be made before the end of the fourth month of pregnancy. The second, third and fourth visits are scheduled at 24–28, 32 and 36 weeks, respectively. Male involvement in Antenatal health care has been described as a process of social and behavioural change that is needed for men to play more responsible roles in maternal health care to ensure women's and children’s wellbeing. A study by Okoth [1] reported that, in Uganda, male involvement in antenatal care stands at only 6% and this has been attributed to social, economic and cultural related factors. The situation worsens with the lack of an effective coordinated platform for males sharing their experience in taking part in ANC and this has affected the process of antenatal care service delivery. Objective. To assess the role of mobile technology in improving male involvement in antenatal care by developing a mobile-based technology which sends SMS reminders to male partners encouraging them to escort their pregnant wives for antenatal care services. Research questions. What are the challenges towards the limited antenatal care-seeking behaviours among pregnant mothers? What are the causes of limited male involvement in antenatal care? What roles do ICTs play in enhancing Antenatal Care seeking behaviours among pregnant mothers and in increasing the male involvement in Antenatal Care? Method. We purposively selected pregnant mothers whose phones, had been receiving antenatal care services from Kabale General Hospital and reported staying with their male partners. The recruited participants were interviewed together with their male partners. STATA 13 software was used to define participants’ demographics while qualitative data were analysed using content analysis to come up with classes describing participants’ perceptions. Results. Participants reported that reminding them of their next antenatal visit via SMS reminder plays a significant role towards their antenatal care-seeking behaviour. Conclusion. Mobile health could be a potential approach to improving male involvement in antenatal care through sending timely SMS reminders to both the expectant mother and her male partner reminding them of their next antenatal visit.